Epidermoid cyst within an intrapancreatic accessory spleen. (5th April 2018) - Paredes, Anghela; Beal, Eliza Wright; Dillhoff, Mary E
Abstract : This is a case of an epidermoid cyst in an intrapancreatic accessory spleen at the tail of the pancreas. Concurrent epidermoid cyst within the accessory spleen is an exceedingly rare entity. The patient initially presented with abdominal pain, nausea and vomiting. Imaging studies revealed a 3.6 cm cystic mass in the tail of the pancreas that was concerning for a mucinous cystic neoplasm (MCN). The patient underwent a robotic distal pancreatectomy for a suspected diagnosis of MCN, which following histologically examination was found to be an epidermoid cyst of an intrapancreatic accessory spleen. Further imaging characteristics are needed to characterise and differentiate these lesions from those of malignant potential. Robotic distal pancreatectomy is a safe alternative with many benefits including decreased length of stay and decreased blood loss.